2016
DOI: 10.1371/journal.pone.0159392
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Collaborative Research: A Case Study on Linking Science to Farmers’ Perceptions and Knowledge on Arabica Coffee Pests and Diseases and Its Management

Abstract: The scientific community has recognized the importance of integrating farmer’s perceptions and knowledge (FPK) for the development of sustainable pest and disease management strategies. However, the knowledge gap between indigenous and scientific knowledge still contributes to misidentification of plant health constraints and poor adoption of management solutions. This is particularly the case in the context of smallholder farming in developing countries. In this paper, we present a case study on coffee produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 70 publications
5
28
0
Order By: Relevance
“…This analysis showed that only two significantly different groups of ranking estimates were identified for both WCSB and CLR, whereby Cordia africana, A. coriaria, and Ficus mucuso represented the first group (labelled as 'high'), and all the others species were found in the second group (labelled as 'medium'). This means that except for these three highest ranked species, there was no consensus in the rankings of the other species for these two locally important P&D and confirms that local knowledge about specific companion tree species and their relationships to coffee P&D dynamics is scarce as explained by Liebig et al (2016). Cordia africana was exceptionally well ranked for all altitudes and ES (except food) and was followed by the four Ficus species and A. coriaria.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…This analysis showed that only two significantly different groups of ranking estimates were identified for both WCSB and CLR, whereby Cordia africana, A. coriaria, and Ficus mucuso represented the first group (labelled as 'high'), and all the others species were found in the second group (labelled as 'medium'). This means that except for these three highest ranked species, there was no consensus in the rankings of the other species for these two locally important P&D and confirms that local knowledge about specific companion tree species and their relationships to coffee P&D dynamics is scarce as explained by Liebig et al (2016). Cordia africana was exceptionally well ranked for all altitudes and ES (except food) and was followed by the four Ficus species and A. coriaria.…”
Section: Resultsmentioning
confidence: 78%
“…The selected farmers are situated within an area of 210 km 2 ( Fig. 1 (Liebig et al 2016)). The mean annual rainfall in the study area ranges from 1200 to 1400 and 1800 mm and the mean annual temperatures are 23, 21 and 18°C, at respectively low, mid and high altitudes (Hijmans et al 2005).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The Mt. Elgon region has Arabica Coffee farmlands with varying cropping intensities, and semi-natural vegetation that exists in mosaical patterns under variable habitat management approaches within different altitudes (Karungi et al, 2018;Liebig et al, 2016). There are reports of response of specific insect herbivores and generalist predators to cropping complexities in the region (Jonsson et al, 2014;Karungi et al, 2018Karungi et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%